'Between the devil of the desert and the deep blue sea': re-orienting Kuwait, c.1900–1940. (October 2015) - Fletcher, Robert S.G.
Abstract: This article examines the place of two environmental regimes – the desert and the sea – in the history of Kuwait before oil. Historians have long approached Kuwait through its maritime past, foregrounding its connections around the Persian Gulf and across the Indian Ocean. This article shifts the emphasis, arguing that in the early twentieth century Kuwait faced westwards across the desert as much as it did across the sea. It takes this possibility as an opportunity to revisit a set of assumptions about the shape of the pre-oil Kuwaiti economy, the structure of its politics, and the nature of its position within a wider British Empire. In all three, the interwar years in particular witnessed a loosening of Kuwait's maritime bonds and a turn to the desert: an orientation which helped the state survive the difficult years preceding the coming of oil revenues. In part, this act of re-orientation seeks to advance our knowledge of Kuwait before oil, a period and place still neglected by many commentators and scholars. But it also forms part of a wider concern to treat 'empty' desert and steppe 'spaces' as arenas of activity in their own right, capable of exerting significant influence on the polities around them. More broadly, then, Kuwait provides an excellent place to test the power and reach of desert dynamics, and to explore the interplay between maritime and desert influences in global history. Highlights: Uses an environmental history approach to place Kuwait at the intersection of the desert and Indian Ocean worlds. Offers new insights in the history of Kuwait's economy, politics and external relations before oil. Reconsiders the interplay of maritime and desert influences in the imperial and global past.